2021
DOI: 10.2495/eres210061
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Adequacy of Separation Gaps Between Adjacent Buildings Under Near-Field and Far-Field Earthquakes

Abstract: Earthquake-induced pounding is a phenomenon that has been observed in almost every major earthquake since the 1960s. Pounding between adjacent buildings occurs due to insufficient separation and with different dynamic properties. This usually causes local damage, and in some extreme cases, total collapse of structures. Building codes in seismically active zones recommended a minimum separation gap between adjacent buildings to avoid pounding during severe earthquakes. AS1170.4-2007 is an Australian standard th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…Moreover, the DDC and Australian Code formulas provided overestimate, accurate, and underestimate results, and the SRSS formula provided both accurate and overestimated results. Similar findings were reported concerning the Australian Code formula (Equation ( 5)) as it was found that it provides accurate results only in the case of the far-field earthquakes considering the in-between gap equal to 1% of the height of the taller building and not related to the height of the shorter building (see [76] for details). In the case of near-field earthquakes, or in the case when the gap was considered as equal to 1% of the height of the shorter building, the Australian Code formula (Equation ( 5) provides inaccurate results and underestimates the gap [76].…”
Section: Introductionsupporting
confidence: 84%
“…Moreover, the DDC and Australian Code formulas provided overestimate, accurate, and underestimate results, and the SRSS formula provided both accurate and overestimated results. Similar findings were reported concerning the Australian Code formula (Equation ( 5)) as it was found that it provides accurate results only in the case of the far-field earthquakes considering the in-between gap equal to 1% of the height of the taller building and not related to the height of the shorter building (see [76] for details). In the case of near-field earthquakes, or in the case when the gap was considered as equal to 1% of the height of the shorter building, the Australian Code formula (Equation ( 5) provides inaccurate results and underestimates the gap [76].…”
Section: Introductionsupporting
confidence: 84%
“…Therefore, the study highly recommends performing similar studies for buildings with mat foundation systems. Similar findings from (Elwardany et al, 2019;Jaradat et al, 2021;Awchat et al, 2022) emphasized the importance of including SSI effects in the calculation for the pounding impacts.…”
Section: Wall-frame Structuressupporting
confidence: 61%
“…In their study, Jaradat et al [50,51] conducted experiments and numerical analyses to assess the effectiveness of the Australian standard AS1170. in mitigating seismic pounding between steel frame structures during near-field and far-field earthquakes.…”
Section: Introductionmentioning
confidence: 99%